2019
DOI: 10.1021/acsnano.9b02071
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Nanoadjuvant-Assembled Tumor Vaccine for Preventing Long-Term Recurrence

Abstract: Although immune checkpoint inhibitors have emerged as a breakthrough in cancer therapy, a monotherapy approach is not sufficient. Here, we report an immune checkpoint inhibitor-modified nanoparticle for an in situ-assembled tumor vaccine that can activate immune systems in the tumor microenvironment and prevent the long-term recurrence of tumors. Adjuvant-loaded nanoparticles were prepared by entrapping imiquimod (IQ) in photoresponsive polydopamine nanoparticles (IQ/PNs). The surfaces of IQ/PNs were then modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 56 publications
2
90
0
Order By: Relevance
“…Our studies of the protective efficacy of vaccination in mice challenged twice with B16-OVA tumor cells showed that suppression of challenged tumor growth was attributable to the increased infiltration of both CD4(+) and CD8(+) T lymphocytes into the tumor tissues. The long-term tumor-preventive effect observed in OVA and RA/CTS polyplex-vaccinated mice could be explained by the increase in effector memory T cells [13,37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our studies of the protective efficacy of vaccination in mice challenged twice with B16-OVA tumor cells showed that suppression of challenged tumor growth was attributable to the increased infiltration of both CD4(+) and CD8(+) T lymphocytes into the tumor tissues. The long-term tumor-preventive effect observed in OVA and RA/CTS polyplex-vaccinated mice could be explained by the increase in effector memory T cells [13,37].…”
Section: Discussionmentioning
confidence: 99%
“…BMDCs were isolated and differentiated from monocytes as previously described, with minor modifications [13]. Briefly, femurs and tibiae from 6-week-old C57BL/6 mice (Raon Bio, Yongin, Kyonggi-do, Korea) were isolated and flushed with complete RPMI media to collect bone marrow.…”
Section: Isolation Of Bone Marrow-derived Dendritic Cells (Bmdcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study, Le et al demonstrated that coating the surface of nanoparticles containing imiquimod and photosensitizer with anti‐PD‐L1 antibody can significantly increase nanoparticle accumulation in tumors overexpressing PD‐L1. [ 29 ] They represented a sequence of transmission electron microscopy (TEM) images that demonstrated the presence of nanoparticles on tumor cell surface sensitizes tumor cells to irradiation‐induced ICD and generates antitumor immunity (Figure 1B). This in situ‐generated tumor vaccine, when combined with additional anti‐PD‐L1 antibodies, successfully prevented long‐term recurrence for up to 150 d after the primary tumor was discovered.…”
Section: Photothermal Therapy and Its Immunomodulatory Effectmentioning
confidence: 99%
“…Yang et al [52] reported the use of a lipid (DSPE-PEG-mannose) modified cancer cell membrane that was coated onto a polymeric NP loaded with adjuvant TLR 7 for an anticancer effect [52]. Recently, Le et al [92] suggested an in situ nanoadjuvant as a tumor vaccine to prevent the long-term recurrence of tumors. In their study, polydopamine NPs were loaded with imiquimod, and then the NP surface was modified with programmed death-ligand 1 (PDL1) antibodies for the co-delivery of both antigen and adjuvants to the same antigen-presenting cells.…”
Section: Components Of Biomimetic Immunomodulatory Nanovaccinesmentioning
confidence: 99%